Carbonic anhydrase IX is a pH-stat that sets an acidic tumour extracellular pH in vivo - Lee, Shen-Han (Br J Cancer, 2018)
BACKGROUND: Tumour carbonic anhydrase IX (CAIX), a hypoxia-inducible tumour-associated cell surface enzyme, is thought to acidify the tumour microenvironment by hydrating CO(2) to form protons and bicarbonate, but there is no definitive evidence for this in solid tumours in vivo. METHODS: We used (1)H magnetic resonance spectroscopic imaging (MRSI) of the extracellular pH probe imidazolyl succinic acid (ISUCA) to measure and spatially map extracellular pH in HCT116 tumours transfected to express CAIX and empty vector controls in SCID mice. We also measured intracellular pH in situ with (31)P MRS and measured lactate in freeze-clamped tumours. RESULTS: CAIX-expressing tumours had 0.15 pH-unit lower median extracellular pH than control tumours (pH 6.71 tumour vs pH 6.86 control, P = 0.01). Importantly, CAIX expression imposed an upper limit for tumour extracellular pH at 6.93. Despite the increased lactate concentration in CAIX-expressing tumours, (31)P MRS showed no difference in intracellular pH, suggesting that CAIX acidifies only the tumour extracellular space. CONCLUSIONS: CAIX acidifies the tumour microenvironment, and also provides an extracellular pH control mechanism. We propose that CAIX thus acts as an extracellular pH-stat, maintaining an acidic tumour extracellular pH that is tolerated by cancer cells and favours invasion and metastasis.